Tectono-magmatic processes in the internal zones of the Variscan Orogen: the Tomiño area (NW Iberian Peninsula) - Toyos, J. M.; González Menéndez, L. V. (TRABAJOS DE GEOLOGÍA, 2010)
In the NW Iberian Variscan Belt we have surveyed a zone with an unusual development oflate D3 ductile structures (Tomiño area, Pontevedra). The rocks studied are mainly schists and granitoids.An early tectonic phase of folding (D1) was almost completely obliterated by a later one (D3).Syn-kinematic P-T estimations point to ~4 kbar and ~565 ºC. These HT conditions and the abundanceof granitic magmas would have imposed crustal weakening during the D3 contractional event.Under this high heat flux, ductile D3 structures were easily developed.